Artificial Intelligence and Computational Intelligence Third International Conference, AICI 2011, Taiyuan, China, September 24-25, 2011, Proceedings, Part III - Deng, Hepu; Miao, Duoqian; Lei, Jingsheng; Wang, Fu Lee (Springer eBooks., 2011)
This three-volume proceedings contains revised selected papers from the Second International Conference on Artificial Intelligence and Computational Intelligence, AICI 2011, held in Taiyuan, China, in September 2011. The total of 265 high-quality papers presented were carefully reviewed and selected from 1073 submissions. The topics of Part III covered are: machine vision; natural language processing; nature computation; neural computation; neural networks; particle swarm optimization; pattern recognition; rough set theory; and support vector machine.